The public ledger: commodity Year Book (New York Commodity Research Bureau, 1982)
This is prices for most major commodities both foodstuffs and industrial raw materials registered significant declines in 1981.
aia 13/02/2019
Loans
Keywords: Commercial product -- United States; Commercial product -- Statistics--Periodicals